Performance analysis of Zomba water users' association in rural water supply schemes: A focus on financial, operational, and customer perspectives - Chilanga, Temwa (Mzuzu University, 2024)
Water utilities in developing countries are locked in a vicious cycle, with weak operational and financial capacity, leading to performance failures and inefficiencies. Water Users Associations (WUAs) have been adopted in Malawi to govern rural water supply systems. This study aimed to evaluate the performance of WUAs in Zomba and devise strategies for sustained improvements in water delivery services. Specific objectives were to: assess the performance of WUAs in financial, customer, and operational performance indicators and examine factors influencing the WUAs. The study adopted a mixed-method research design. Seven WUAs were targeted in Zomba of which one was dissolved. Questionnaires, key informant interviews, and focus group discussions were used to collect data on performance measures of the utilities, customer perceptions, and factors influencing performance. SPSS and Microsoft Excel software and thematic analysis were used in data analysis. Results displayed poor financial performance as only one WUA hit a working ratio of 1.1 while the rest operated on negative accounts. The majority further faced challenges in revenue collection. Compromised water quality due to lack of chlorination was displayed in two thirds of the WUAs and customers complained of turbid water during the rainy season in all WUAs due to lack of filters. On tariffs, 73% of customers found the pricing reasonable whilst on the overall customer satisfaction, 95% of customers were satisfied. It was found that all WUAs, except one, were unable to quantify their water losses and none had hit the target of the staff-efficiency measure. The study concluded that the WUAs were mostly affected by a lack of supportive policies, poor governance, a low revenue base, and aging infrastructure. Therefore, it is recommended that the WUAs deserve post-construction support from the government and other key players to enhance the sustainability of rural water supply schemes in Malawi.